Evolving Practice and Changing Phenotype in Pediatric Autoimmune Liver Disease: Outcomes From an Australian Center. Issue 1 (July 2018) - Singh, Harveen; Balouch, Fariha; Noble, Charlton; Lewindon, Peter
ABSTRACT: Objectives: Autoimmune liver disease (AILD) incorporates primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), and autoimmune sclerosing cholangitis (ASC). ASC is a condition that includes overlap of AIH and PSC. We investigate changes in practice in relation to diagnosis and phenotype over 2 time periods. Methods: Retrospective chart review was conducted from January 2000 to 2016. Data were divided into two 8-year cohorts, CI and C2. Results: Data were collected in 75 children, 29 in 2000–2007 (C1) and 46 in 2008–2016 (C2). Presenting AILD type was AIH in 59%, ASC in 10%, and PSC in 31%. Final AILD type was AIH in 53%, ASC in 16%, and PSC in 31%. When comparing C1 to C2, those with AIH decreased (65% vs 45%) and those with ASC increased (14% vs 18%). Use of magnetic resonance cholangio-pancreatography increased from 34% in C1 to 65% in C2. Advanced liver disease on biopsy was noted in 53% of all children at presentation. Only 5 female children progressed to liver transplant (3 ASC-IBD [inflammatory bowel disease]; 1 PSC-IBD; 1 AIH). Colonoscopy performance increased from 48% in C1 to 63% in C2 with diagnosis of AILD-IBD increasing from 31% to 52%. Right-sided disease was present in 46% and macroscopic rectal sparing in 36% of those with ulcerative colitis (UC). Colectomy was required in 3 children with large duct PSC-IBD. Conclusions: PSC and ASC are increasing in relevance along with IBD and reflect increasing performance of magnetic resonance cholangio-pancreatography and colonoscopy. Large duct PSC and ASC with IBD are risk factors for colectomy and along with female gender, for liver transplant.